Relationship between the number of lost teeth and the occurrence of depressive symptoms in middle-aged adults: a cross-sectional study - Martyna Głuszek-Osuch; Elżbieta Cieśla; Edyta Suliga (BMC, 2024)
Abstract Background Many recent studies suggest the existence of a relationship between oral health and the occurrence of depressive symptoms. The aim of this study was to assess the relationship between the number of lost teeth and the occurrence of depressive symptoms in middle-aged adults. Methods An analysis was performed on the data obtained from the PONS project (POlish-Norwegian Study), conducted in the Świętokrzyskie Province in Poland in 2010-2011. The research material included the cross-sectional data of 11,901 individuals aged 40-64 years (7967 women). Depressive symptoms, used as outcome variables, were assessed with a questionnaire. The participants provided the responses to questions concerning the occurrence of eight symptoms over the last 12 months. The answers were scored as 1 point or 0 points. The participants were divided into three tercile groups based on their total scores: no or mild (0-2 points), moderate (3-5 points), and severe depressive symptoms (6-8 points). The self-reported number of lost teeth was analysed according to the following categories: 0-4, 5-8, 9-27, and a complete lack of natural teeth. Multivariable logistic regression analysis for depressive symptoms was used in relation to the number of lost teeth. The following covariates were included in the adjusted model: age, sex, place of residence, education, marital status, BMI, diabetes status, stressful life events in the last year, use of antidepressants, smoking, and sugar and sweet consumption. Results The likelihood of both moderate (OR = 1.189; 95%CI: 1.028-1.376; p < .020) and severe (OR = 1.846; 95%CI: 1.488-2.290; p < .001) depressive symptoms showed the strongest relationship with a total lack of natural teeth. A loss of more than 8 natural teeth was also significantly associated (OR = 1.315; 95%CI: 1.075-1.609; p < .008) with the occurrence of severe depressive symptoms. Conclusions The loss of natural teeth was positively related to the occurrence of depressive symptoms in middle-aged adults. Thus, there is an urgent need to intensify stomatological prophylaxis, education and treatment for middle-aged individuals.